Prehistoric Occupation of Banyoles Lakeshore: Results of Recent Excavations at La Draga Site, Girona, Spain. (September 2014) - Palomo, Antoni; Piqué, Raquel; Terradas, Xavier; Bosch, Àngel; Buxó, Ramon; Chinchilla, Júlia; Saña, Maria; Tarrús, Josep
Abstract : Recent research at the Neolithic site of La Draga on the edge of Banyoles Lake (Girona, Spain) has documented evidence for the occupation of the lakeshore from the final quarter of the sixth millennium cal BC. Excavation during 2010 and 2011 identified at least two episodes of occupation. The oldest episode includes wooden structures, which were superseded and overlain by a paving of travertine blocks during the younger phase. Archaeological materials, artefacts, and pottery styles indicate a level of continuity between the two phases of construction and occupation. Both episodes can be attributed to the Cardial Neolithic. Investigation of the underwater part of the site resulted in the discovery of the first wooden tools from the site and therefore from the prehistory of Iberia.